2020
DOI: 10.1017/ice.2020.42
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinicians’ knowledge, attitudes, and planned behaviors related to an intervention to improve acute respiratory infection management

Abstract: Background:Acute respiratory tract infections (ARIs) are commonly diagnosed and major drivers of antibiotic prescribing. Clinician-focused interventions can reduce unnecessary antibiotic prescribing for ARIs. We elicited clinician feedback to design sustainable interventions to improve ARI management by understanding the mental framework of clinicians surrounding antibiotic prescribing within Veterans’ Health Administration clinics.Methods:We conducted one-on-one interviews with clinicians (n = 20) from clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Recent qualitative research on this area has explored service users' [32] and prescribers' [33][34][35][36][37] attitudes towards delayed antibiotic prescription, prescribers' attitudes and experiences on antibiotic prescribing [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], service users' experiences on antibiotic use [38,39,48,51,[55][56][57][58], self-care treatments for ALRTIs [32,59], service users' [48,60] and health professionals' [47,48] understandings of AMR and antibiotic use, interactions between health Committee of the Institut de Recerca en Atenció Primària Jordi Gol i Gurina (IDIAPJGol) (contact via cei@idiapjgol.info) for researchers who meet the criteria for access to confidential data. For more information on data availability restrictions you can contact the ethics committee at cei@idiapjgol.info.…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative research on this area has explored service users' [32] and prescribers' [33][34][35][36][37] attitudes towards delayed antibiotic prescription, prescribers' attitudes and experiences on antibiotic prescribing [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], service users' experiences on antibiotic use [38,39,48,51,[55][56][57][58], self-care treatments for ALRTIs [32,59], service users' [48,60] and health professionals' [47,48] understandings of AMR and antibiotic use, interactions between health Committee of the Institut de Recerca en Atenció Primària Jordi Gol i Gurina (IDIAPJGol) (contact via cei@idiapjgol.info) for researchers who meet the criteria for access to confidential data. For more information on data availability restrictions you can contact the ethics committee at cei@idiapjgol.info.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to prescribe antibiotics is complex and influenced by many clinical and nonclinical factors. 8,[26][27][28] Nevertheless, our findings suggest that working with patients to understand what drives expectations could inform patient-focused interventions to reduce URI prescribing. Previous research has shown that it is feasible to change patients' expectations for antibiotics for URIs.…”
Section: Discussionmentioning
confidence: 88%
“…3 Many providers perceive that patients desire or expect antibiotics, 4,5 which strongly influences provider prescribing. [6][7][8] Although patient expectations for antibiotics may be decreasing over time, 5,9 a reported 50%-72% of patients expect antibiotics for URI-like symptoms. 6,[10][11][12] Many studies have shown increased patient satisfaction associated with antibiotic receipt; [13][14][15] others showed no association.…”
mentioning
confidence: 99%
“…This sample is highly educated, often practices full-time in adult care specialties across inpatient and outpatient settings and is not a frequent antibiotic prescriber. Similar to other studies, most of the NPs are knowledgeable about the association between antibiotic overuse and the development of AR infections, as well as the importance of using evidence-based guidelines for prescribing antibiotics to optimize patient outcomes (Hamilton et al, 2020; Hruza et al, 2020; Knobloch et al, 2021). Surprisingly, almost 18% of participants failed to recognize that antibiotics are powerful drugs that carry a wide range of adverse effects, making this an important area to emphasize in any related educational offering.…”
Section: Discussionmentioning
confidence: 89%